DAMPAK AMANDEMEN UNDANG-UNDANG NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP KEMERDEKAAN BEREKSPRESI - Ilham Gemiharto; Firman Alamsyah Taufik Robbi (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Globalization of information has placed Indonesia as part of the world information community, therefore the implementation of the Information and Electronic Transaction Law aims to develop Information Technology optimally, distributed to all levels of society to advance people's intellectual life. The enactment of such a strict law is basically a manifestation of the nature of the electronic transaction itself, which is global and without limits. Elucidation of article 2 further explains the nature of this jurisdictional law, and states that the use of Information Technology for Electronic Information and Electronic Transactions is cross-territorial or universal, so that this law has jurisdiction over legal actions that apply not only in Indonesia or carried out by citizens country of Indonesia, but also applies to legal actions carried out outside Indonesian jurisdiction by Indonesian citizens and foreign nationals or Indonesian legal entities and foreign legal entities that have legal effect in Indonesia.